Percutaneous calcium sulfate injection versus localized scrape bone grafting: clinical effect comparison in titanium elastic nail treatment of pathological fracture of proximal humerus caused by unicameral bone cysts in children - Xie, Yuyin; Song, Zhenqi; Tang, Zhongwen; Xu, Zheng; Rao, Zhouzhou; Wen, Jie; Xiao, Sheng (Frontiers in Pediatrics, 2024)
Objective: A retrospective study was conducted to compare the mid-term clinical efficacy between percutaneous calcium sulfate injection (PCSI) and localized scrape bone grafting (LSBG) in using titanium elastic nails treat humerus pathologic fractures caused by unicameral bone cysts in children. Methods: Humerus pathologic fracture patients with unicameral bone cysts in our pediatric orthopedic department from January 2015 to January 2020 were retrospectively analyzed. Patients were divided into two groups, namely the PCSI group and the LSBG group, based on the type of bone grafting material they received. Preoperative assessments were made in both groups using the Cyst Index and Cyst activity. During the perioperative phase, assessments were made regarding operative time, bleeding, postoperative VAS scores, and the frequency of reoperation within 2 years. Clinical outcomes were evaluated using the Capanna scale at the last follow-up, and the occurrence of re-fractures during the follow-up period. Results: A total of 22 patients were included, with a mean follow-up duration of 33.5±5.8 months. No significant differences were found between the two groups in terms of Cyst Index and Cyst activity before the operation. The operative time, bleeding, and postoperative VAS scores in the PCSI group were found to be lower than those in the LSBG group (P < 0.05). The PCSI group also showed a higher frequency of reoperation within 2 years compared to the LSBG group (P < 0.05). However, no significant differences were observed between the two groups in terms of Capanna scale scores at the last follow-up and the incidence of re-fractures during follow-up. Conclusions: Both titanium elastic nails (TEN) combined with PCSI or LSBG were found to be safe and effective treatments for humerus pathologic fractures caused by unicameral bone cysts in children. PCSI is considered as a less invasive option with shorter operative times, less bleeding, and reduced postoperative pain, although it comes with the risk of multiple injections. On the other hand, LSBG is considered as a more invasive option for the treatment of active bone cysts but is associated with a lower recurrence rate.